Verbal Fluency Deficits Co-Occur with Memory Deficits in Geriatric Patients at Risk for Dementia: Implications for the Concept of Mild Cognitive Impairment - Maria E. Cottingham; Keith A. Hawkins (Behavioural Neurology)
We tested the notion that patients at high risk for progression to Alzheimer's disease (AD) display relatively isolated memory deficits by assessing the relationship between memory and fluency performances in a sample of 92 geriatric subjects with cognitive complaints and normal to mild clinical presentations. Patient groups were formed on the basis of memory test scores. Patients with normal memory scores also performed normally on fluency tests, and their fluency scores were significantly higher than those of patients with low memory performances. Patients falling between these two groups in memory abilities also displayed intermediate level fluency performances. Whereas the normal memory group performed at equivalent levels on semantic and phonemic fluency tasks, both the impaired memory group and the intermediate group displayed relatively greater weaknesses in semantic fluency. This pattern is similar to that seen in AD. Since the impaired memory patients meet criteria for Amnestic Mild Cognitive Impairment, these findings suggest that memory deficits in “pre-clinical” AD are likely to be accompanied by fluency weaknesses, with semantic fluency weaknesses predominating.